PENERAPAN ELECTRONIC LEARNING MELALUI MEDIA AUDIO VISUAL TERHADAP HASIL SHOOTING THREE POINT DALAM OLAHRAGA BOLABASKET ( STUDI PADA SISWA KELAS XI IPA 2 SMA NEGERI 2 KOTA MOJOKERTO ) - YUDHA ADYRAMA, AKHMAD (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Basketball learning is one of basic competence which is included in sport learning at school, therefor at will be able to increase the student’s quality in the basketball learning is needed the varieties and interested learning models to encourage the students feel happy and pleasure, so their capability in basketball will increase. One of the basic technic form in basketball is shooting three point. The goal of this research is to know the increasing of the students capability in giving this material about shooting three point in basketball study to the students of XI science 2 SMAN 2 Mojokerto by applying electronic learning with Audio Visual Media. This research use Randomized Control Group Pretest-Posttest Design because this design is merely perfect. In this case using 3 components ; control group, action and subject which is placed Randomly. Pretest-Posttest given to make sure the effectively of the action. The Result of this Research shows that the applying of electronic learning by using of audio Visual give the positive increasing Rate to the experiment group 5 points and 3 points for control group. Keywords: basketball, Audio Visual, shooting three point.